A causal relationship between childhood obesity and risk of osteoarthritis: results from a two-sample Mendelian randomization analysis - Cao, Ziqin; Wu, Yudi; Li, Qiangxiang; Li, Yajia; Wu, Jianhuang (Annals of medicine (Helsinki), 2022)
It has been found that childhood obesity (CO) may play an important role in the onset and progression of osteoarthritis (OA). Thus we conducted this mendelian randomisation analysis (MR) to evaluate the causal association between childhood obesity and osteoarthritis. Instrumental variables (IVs) were obtained from publicly available genome-wide association study datasets. The leave-one-out sensitivity test, MR Pleiotropy RESidual Sum and Outlier test (MR-PRESSO), and Cochran's Q test were used to confirm the heterogeneity and pleiotropy of identified IVs, then five different models, including the inverse variance weighted model (IVW), weighted median estimator model (WME), weighted model-based method (WM), MR-Egger regression model (MER), and MR-Robust Adjusted Profile Score (MRAPS) were applied in this MR analysis. After excluding all outliers identified by the MR-PRESSO test, no evident directional pleiotropy was found. Significant heterogeneity was found in the secondary MR and as a result, the multiplicative random-effect model was used. Significant causal association between CO and OA (OR 1.0075, 95% CI [1.0054, 1.0010], p = 8.12 × 10 −13 ). The secondary MR also revealed that CO was causally associated with knee OA (OR 1.1067, 95% CI [1.0769, 1.1373], p = 3.30 × 10 −13 ) and hip OA (OR 1.1272, 95% CI [1.0610, 1.1976], p = 1.07 × 10 −4 ). The accuracy and robustness of these findings were confirmed by sensitivity tests. There appears to be a causal relationship between childhood obesity and OA. Our results indicate that individuals with a history of childhood obesity require specific clinical attention to prevent the development of knee and hip OA.